2021
DOI: 10.26594/register.v8i1.2356
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy-AHP MOORA approach for vendor selection applications

Abstract: Vendor selection is a critical activity in order to support the achievement of company success and competitiveness. Significantly, the company has some specific standards in the selection. Therefore, an evaluation is needed to see which vendors match the company's criteria. The purpose of this study is to evaluate and select the proposed vendor in a web-based decision support system (DSS) by using the fuzzy-AHP MOORA approach. The fuzzy-AHP method is used to determine the importance level of the criteria, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Various methods have been proposed for this purpose. For instance, the fuzzy analytic hierarchy process (AHP) and MOORA techniques have been used to evaluate and select vendors [ 24 ]. The fuzzy MOORA (FMOORA) approach has been employed to assess the potential for mushroom farming [ 25 ], and MOORA has been used to select the best teachers and staff [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various methods have been proposed for this purpose. For instance, the fuzzy analytic hierarchy process (AHP) and MOORA techniques have been used to evaluate and select vendors [ 24 ]. The fuzzy MOORA (FMOORA) approach has been employed to assess the potential for mushroom farming [ 25 ], and MOORA has been used to select the best teachers and staff [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, a comparative study of Pythagorean fuzzy MOORA and TOPSIS methods was performed to rank the suppliers’ options. Khoiry et al [ 135 ] proposed a decision-making framework integrating fuzzy-AHP and MOORA methods for good vendor selection. The results were validated by sensitivity analysis and confirmed the robustness of the hybrid approach.…”
Section: Application Areasmentioning
confidence: 99%
“…The literature review shows that several researchers [20][21][22][23][24][25][26][27][28][29][30] have proposed different tools as well as models that are used in the GSD context. Rahman et al [15] suggested a model based on the factors that are used to help IT experts in taking decisions in the global delivery context.…”
Section: Study Backgroundmentioning
confidence: 99%